2022
DOI: 10.3389/fgene.2022.1032110
|View full text |Cite
|
Sign up to set email alerts
|

Association between OPG polymorphisms and osteoporosis risk: An updated meta-analysis

Abstract: Background: Numerous studies have demonstrated an association between osteoprotegerin (OPG) polymorphisms (A163G (rs3102735), T245G (rs3134069), T950C (rs2073617), G1181C (rs2073618)) and osteoporosis risk. However, their conclusions are inconsistent. In addition, some new studies have been updated, and more importantly, previous meta-analyses have not tested for false-positive results. In order to further explore these associations, we recently conducted a meta-analysis.Objectives: To study the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
3
3
0
Order By: Relevance
“…A meta-analysis conducted in 2022 by Han et al, taking into account all studies conducted to date, also found no effect of the osteoprotegerin rs3134070 polymorphism on the incidence of osteoporosis, which is in line with the conclusions drawn from this study [10].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A meta-analysis conducted in 2022 by Han et al, taking into account all studies conducted to date, also found no effect of the osteoprotegerin rs3134070 polymorphism on the incidence of osteoporosis, which is in line with the conclusions drawn from this study [10].…”
Section: Discussionsupporting
confidence: 89%
“…A comprehensive meta-analysis performed in 2022 by Han et al, where they analyzed the results of most of the above studies as well as previously performed meta-analyses, showed that all significant associations between OPG rs3102735 polymorphisms and increased osteoporosis risk tended to be false positives, which is in line with the results obtained in this paper [10].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The evaluation criteria of studies quality were shown in Table S1, Supplemental Digital Content, http://links.lww.com/MD/K138 according to previous studies. [ 53 55 ] Two authors assessed the studies quality, respectively. The total score was 21 points, studies scoring > 13 were high quality.…”
Section: Methodsmentioning
confidence: 99%